Manajemen Sumber Daya Manusia Sebagai Pendukung Keberhasilan Kurikulum - Liyadi, Muslim; Lubis, Nasib Samsuri; Mudasir, Mudasir (Jurnal Pusat Studi Pendidikan Rakyat, 2024)
Resources are everything that is an asset to achieve important things in education to achieve goals. The resources owned by a company can be grouped into four types of resources, such as Financial, Physical, Human and Technological Capabilities. Financial resources are an important element in forming a company that is advanced and continues to grow because it is related to shares which are the main capital in building a company and developing and continuing the company or educational institution. Physical resources are resources that include the physical maintenance of an educational institution such as its equipment. Human resources are a central and important sector in achieving goals in the world of education. because of the skill capabilities of teaching staff and educational staff, in this case, HRM plays a very important role in ensuring the successful implementation of the curriculum in educational institutions. The role of HRM is not only limited to administration, but also to developing and empowering human resources that can encourage the achievement of overall educational goals.